Perfil sensorial e químico de genótipos de cafeeiro conilon em resposta ao sombreamento artificial - Littig, Marlete (2023)
The search for quality has been one of the main interests in the production chain of conilon coffee (Coffea canephora), since it has gradually become more important in the commercialization of the product. With the launch of new conilon coffee cultivars, it is important to understand the behavior in relation to full sun and shaded cultivation. Thus, the objective of this work was to characterize and identify alterations in the sensory profile and in the volatile chemical composition of different genotypes of conilon coffee plants, cultivated under conditions of artificial shade and full sun. The experiment was conducted at the Experimental Farm of Bananal do Norte, belonging to Incaper and located in the municipality of Cachoeiro de Itapemirim - ES, and the experimental design used was in randomized blocks, with four blocks, and the treatments were established in a factorial 11x2, being the 11 C. canephora genotypes submitted to two irradiance availabilities, full sun and 30% of artificial shading. The harvest was carried out considering the maturation cycles, the fruits being harvested, dried in a suspended terrace until they reached 12% of humidity, and then processed, with the removal of defects. The sensory profile was evaluated based on the quality of the beverage, according to the Specialty Coffee Association (SCA) sensory analysis methodology. The chemical profile was evaluated using headspace solid phase microextraction combined with gas chromatography coupled to mass spectrometry. Descriptive analyzes were carried out to characterize the genotypes in terms of chemical profile and beverage quality, and Pearson's linear correlations were estimated for the sums of classes of compounds and parameters of beverage quality for the 11 genotypes of conilon coffee cultivated in full sun and under shade. Based on the results, it was possible to prove that: changing irradiance is capable of modifying the sensory profile and chemical composition of volatile compounds in conilon coffee; the variability between conilon coffee genotypes allows identifying different responses to shading; some genotypes (104, 12V, 109, 820/87, 304) show greater changes in their sensory profile and volatile composition than others (103, 2B/88, 108, 604/97, 207, 303), depending on shading . The main classes of chemical compounds identified were furans, pyrazines and phenols. The classes that most correlated with coffee beverage quality parameters were pyrimidines and amines, for full sun cultivation, and pyrazines and phenols, for shaded cultivation.